ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI DAYA KONSENTRASI BELAJAR MENGGUNAKAN EXTENDED COX REGRESSION - Jessica Valenci Soegianto; Triastuti Wuryandari; Agus Rusgiyono (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2026)
Learning concentration plays a major role in the success of teaching and learning activities and is the main asset for students in receiving and mastering the subject matter presented. This study aims to determine the average endurance time of learning concentration power of students in grades 4-6 at SDN 02 Jenarwetan and the factors that influence it. The method used is Cox Extended because there are independent variables that do not meet the Proportional Hazard assumption. Parameter estimation uses the Maximum Partial Likelihood Estimation (MPLE) method with the Efron approach because there is data with co-occurrence. Based on the results of data analysis, the average endurance time of students' learning concentration power is 13.22 minutes. It is also known that the factors that influence the endurance of students' learning concentration power are the level of learning motivation and the level of stress experienced by students. Students with high learning motivation are able to maintain their learning concentration for a long period of time , while students with high stress levels are more at risk of losing learning concentration 4.6294 times higher than students with low stress levels.